Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Structural analysis of protein and identification of key protein during the evolution of whole egg liquid foam - Yuanyuan Zhang; Xiang Fan; Haobo Jin; Yi Sun; Yanli Wang; Erjiao Li; Sadaqat Ali; Yanbin Song; Yunxin Sun; Long Sheng (Food Hydrocolloids, 2026)

Regulation of Tidal Flat Sediment Dynamics by an Ecological Submerged Breakwater: Insights from the Northern Coast of the Sheyang River Estuary, Jiangsu, China - Xiaofei Zhang; Aijun Wang; Xiang Ye; Wanqing Pang; Zhenkun Lin; Yanbin Fan (Journal of Marine Science and Engineering, 2026)
Tidal flats are shrinking and eroding due to sea-level rise and human activities. Ecological submerged breakwaters (ESBs) offer a novel solution combining coastal protection and ecological restoration, but their effects on sediment dynamics lack field evidence. This study presents synchronous in situ measurements from an inner tidal flat (WN01) and an outer shallow area (WN02) of a newly built riprap slope-type ESB on the northern coast of the Sheyang River Estuary, Jiangsu, China. Using Acoustic Doppler Velocimeters (ADVs) and wave-tide gauges, we examined hydrodynamics, suspended sediment concentration (SSC), bed shear stress, erosion–accretion, and sediment transport under normal-weather and strong wave events. Within the constraints of a 14-day observation at two stations, our results indicate that: (1) The ESB reduced wave height and weakened currents, shifting dominant bed shear stress from wave-dominated outside to tide-dominated inside. Under normal weather, both sides were accretive. (2) Strong wave events caused sharp increases in bed shear stress, net erosion on both sides, and a 2–3-fold SSC rise, breaking the normal balance. (3) Suspended sediment transport direction remained northwest inside during strong wave events but shifted to northeast/southeast outside, demonstrating effective isolation of wave-driven anomalies. Bedload was trapped inside, resulting in no net sediment loss, in contrast to the unprotected southern tidal flat. (4) We recommend moderately lowering the ESB crest elevation to prevent excessive accretion and implementing “grey-green” restoration (salt marshes or oyster reefs) to enhance coastal resilience against sea-level rise.

Regulation mechanism of fatty acid chain length and saturation on lipid adsorption behavior and protein conformation during whole egg liquid foam evolution - Yuanyuan Zhang; Yanli Wang; Haobo Jin; Yi Sun; Sadaqat Ali; Erjiao Li; Xiang Fan; Yanbin Song; Yunxin Sun; Guofeng Jin; Long Sheng (Food Hydrocolloids, 2026)

Nonequilibrium fractionation of rare earth elements during typhoon-induced event sedimentation - Yanbin Fan; Yunhai Li; Yunpeng Lin; Haidong Li; Hengbo Wang; Haibo Fan; Hannv Zhang; Guicai Zhong; Feng Jiang (Frontiers in Marine Science, 2026)
High-energy, short-lived typhoon deposition can disrupt particle–water interactions, raising the question of whether rare earth elements (REEs) in event deposits still reflect equilibrium-controlled partitioning or instead capture transient, non-equilibrium geochemical states. We sampled a ~0.5–1 cm surface storm layer and underlying background sediments at 11 stations in the northeastern Beibu Gulf on 29–30 September 2024 (20–21 days after Typhoon Yagi), and quantified major/trace elements and REEs by ICP-OES and ICP-MS, integrating grain size/TOC and statistical correlations. Storm deposits show systematically lower ∑REE and LREE concentrations and slightly lower LREE/HREE ratios than background sediments, accompanied by weaker negative Eu anomalies and a shift toward slightly negative Ce anomalies relative to the mild positive Ce anomaly in background deposits. Despite finer textures and elevated TOC in the storm deposits, the canonical grain-size/adsorption control collapses, with ∑REE exhibiting little to no correlation with grain-size under storm conditions. Critically, storm deposits display pronounced LREE–HREE decoupling: LREE behave quasi-conservatively with “event-scale inertia”, whereas HREE respond more sensitively to non-equilibrium carrier reorganization and rapid settling. This selective decoupling provides a diagnostic geochemical fingerprint for identifying event-driven sedimentation and highlights the need to incorporate kinetic/time-scale effects when interpreting REE-based proxies in dynamic environments.

Mechanistic Links Between Suspended Sediment Dynamics and Metal Partitioning Under Tidal Forcing: A Case Study of Quanzhou Bay - Yanbin Fan; Yunhai Li; Yunpeng Lin; Shangshang Yang; Zhijie Chen; Xiang Cao; Chenyang Wang; Shanshan Zhang; Jinzeng Jiang; Mingyang Jiang; Kaichao Wan (Journal of Marine Science and Engineering, 2026)
The coupling of physical transport and phase-transfer processes represents a fundamental mechanism governing metal cycling in estuarine systems under tidal oscillations. Taking Quanzhou Bay as a model system, we conducted continuous observations and sample collection at the river channel (Q1), the turbidity maximum zone (Q2), and the outer bay channel (Q3). The metals (Al, Ti, Ba, Cu, Mn, and Zn) were measured by ICP-MS to systematically investigate the distribution, transport, and inter-media transfer across multiple water layers under varying estuarine processes. Our findings demonstrate that particulate metal concentrations in Quanzhou Bay exhibit strong synchrony with suspended sediment concentrations (SSC) over tidal cycles, displaying a distinct sediment-following pattern controlled by alternating end members. Particulate metal fluxes during flood and ebb-tides generally followed the hierarchy Q1 > Q2 >> Q3. Notably, stations Q1 and Q2 were dominated by flood-tide fluxes with net transport directed landward, whereas Q3 was characterized by ebb tide dominance with net flux directed seaward—revealing a spatial division of labor between “inner bay retention/reallocation” and “outer bay channel export”. In contrast, dissolved metals exhibited marked element-specific responses to tidal forcing: Al and Ti increased during flood tides at stations Q1 and Q2, while Ba and Cu showed opposite trends, and Mn and Zn displayed more conservative behavior. Concurrently, solid/liquid partition coefficient (logKd) values for Al, Ti and Ba, Cu exhibited inverse patterns over tidal cycles, suggesting divergent adsorption–desorption regulation under identical hydrodynamic conditions that drives differential phase-transfer dynamics. These disparities likely reflect intrinsic chemical properties and source variations among the elements. This study elucidates, at the tidal timescale, the coupled processes of “alternating end-member control—estuarine filter modulation—concurrent channelized export and inner bay retention” in Quanzhou Bay, providing critical process-level insights for metal flux quantification and bay pollution remediation initiatives in an ecological restoration project.

Evaluation of Wave Attenuation Performance of an Ecological Submerged Breakwater in the Sheyang Coastal Zone, Jiangsu Province, China - Yanbin Fan; Xiaofei Zhang; Aijun Wang; Wanqing Pang; Zhenkun Lin; Xiang Ye; Kai Ouyang (Journal of Marine Science and Engineering, 2026)
Under the combined pressures of natural variability and human activities, the area of tidal flats has been gradually decreasing, with most muddy coasts experiencing varying degrees of erosion. The central coast of Jiangsu Province, a world-renowned region for extensive tidal flats, has witnessed intensifying erosion of its muddy coasts in recent years. To mitigate further coastal erosion, an ecological submerged breakwater (ESB) was constructed in the intertidal zone north of the Sheyang River estuary to reduce wave impact on the shoreline. This study evaluates the wave attenuation performance of the ESB based on wave observations conducted at stations deployed on the seaward and landward sides of the structure in May 2025. Results indicate that the breakwater effectively reduces wave height, but its performance exhibits significant dynamic characteristics. During the observation period, the maximum attenuation rate for significant wave height (H1/3) reached 76.3%, with an average rate of 33.8%. Wave dissipation efficiency was closely related to sea state: under calm conditions (H1/3

Thermal performance assessment of coupled soil stratification and groundwater advection effects on vertical borehole heat exchanger - Linlin Zhang; Dongyang Fan; Yanbin Li; Tianhao Yuan; Jun Chen (Geothermics, 2026)

Interannual variability of mid-high-latitude Eurasian ISO and its impact on surface ozone concentration in North China during boreal summer - Shuangyan Yang; Yanbin Fan; Yashu Liu; Qinghan Xu (Climate Dynamics, 2026)

State information entropy optimized particle filter for AUV cooperative localization algorithm under time-varying noise - Lu Liu; Zedong Liang; Yanbin Chen; Yilu Wang; Xiaomeng Zhang; Chengyi Lu; Guang Pan; Quanyong Fan; Zhenyu Fang; Xinxin Guo (Ocean Engineering, 2025)

Deterioration mechanism for the solubility of skimmed egg yolk powder: powder characteristics, rehydration capability and protein structure - Xiang Fan; Yuanyuan Zhang; Yi Sun; Yanbin Song; Yunxin Sun; Sadaqat Ali; Haobo Jin; Long Sheng (Food Chemistry, 2025)

Egg powder: Constraints, methods of enhancing functional properties and innovative applications - Xiang Fan; Mohamed Salama; Yuanyuan Zhang; Sadaqat Ali; Yi Sun; Yanbin Song; Yunxin Sun; Yumeng Shan; Haobo Jin; Long Sheng (Trends in Food Science & Technology, 2025)

An anti-salt bridge-arch evaporator with vertical channel inspired by water spinach for high-flux steam generation through water flow regulation - Yuanlu Xu; Siwen Wang; Yanbin Xin; Tiantian Chen; Baogang Zhao; Yanming Liu; Xinfei Fan (Desalination, 2025)

Synergic solar interfacial evaporation with heterogenous electro-Fenton: A near zero-discharge approach for water purification - Xinfei Fan; Xiaoyu Liu; Xingzu Zhang; Yanbin Xin; Yuanlu Xu; Hongli Ge; Yanming Liu (Chemical Engineering Journal, 2025)

One-step colorimetric immunosensing of foodborne bacteria using static magnet driven magnetophoretic separation and dual noble metal decorated magnetic nanobeads - Ying Ding; Jing Yuan; Nana Jin; Fengzhen Yang; Fan Jiang; Lei Wang; Yanbin Li; Jianhan Lin (Analytica Chimica Acta, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Influence of synergistic/competitive interactions of nonionic emulsifiers and proteins on the foam stability of whole egg liquids: Based on air-water and oil-water dual interface perspectives - Yuanyuan Zhang; Haobo Jin; Yanli Wang; Erjiao Li; Sadaqat Ali; Xiang Fan; Yanbin Song; Yunxin Sun; Long Sheng (Food Hydrocolloids, 2025)

A multimetallic nanozyme enhanced colorimetric biosensor for Salmonella detection on finger-actuated microfluidic chip - Fan Jiang; Nana Jin; Lei Wang; Siyuan Wang; Yanbin Li; Jianhan Lin (Food Chemistry, 2024)

Advanced plasma hydrogel evaporator for efficient solar-driven saline-alkaline water treatment and agricultural application - Jiabao Sun; Yanbin Xin; Tianyu Sun; Bing Sun; Yutong Yang; Qianyu Yang; Xinfei Fan (Chemical Engineering Journal, 2024)

A self-sufficient catalytic nanofiber evaporator for solar-driven efficient water purification through in-situ hydrogen peroxide generation - Bowen Lv; Xin Dong; Yuanlu Xu; Yanbin Xin; Zijian Qin; Chengwen Song; Yanming Liu; Xinfei Fan (Chemical Engineering Journal, 2024)

Construction waste as a filler of denitrification biofilter for nitrate utilization from wastewater: Characteristics, performance, microbial community and soilless culture - Yinzhou Bao; Lijing Bao; Nan Jiang; Xiaoyang Xu; Fan Yu; Haoyu Xing; Wenpei Ye; Peng Zhou; Yanbin Zhu; Shengyang Zheng; Manhong Huang (Bioresource Technology, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Plasma-assisted synthesis of Janus multifunctional solar evaporator for ultra-long-duration freshwater and thermoelectric co-generation - Jiabao Sun; Yanbin Xin; Bing Sun; Qianyu Yang; Xinfei Fan (Chemical Engineering Journal, 2024)

Species sensitivity distribution for nonylphenol: Acute toxicity and ecological risk in Bohai Region - Xuening Wang; Ruicheng Qi; Shang Li; Min Ding; Jingjing Miao; Lianxue Han; Qichao Fan; Yanbin Li; Luqing Pan (Marine Pollution Bulletin, 2024)

Efficient synthesis of L-malic acid by malic enzyme biocatalysis with CO2 fixation - Jianping Shi; Yan Fan; Xinshan Jiang; Xianglong Li; Shang Li; Yanbin Feng; Song Xue (Bioresource Technology, 2024)

Rapid preparation of Janus biomass evaporator by dielectric barrier discharge plasma for high-efficiency desalination and wastewater purification - Jiabao Sun; Yanbin Xin; Zhi Li; Bing Sun; Xinfei Fan (Chemical Engineering Journal, 2024)

Positive impacts of dietary prebiotic inulin on growth performance, antioxidant capacity, immunity, and intestinal microbiota of red swamp crayfish (Procambarus clarkii) - Qian Wang; Yanbin Lin; Heng Zhang; Wenhao Fan; Shengxuan Li; Guoliang Ruan; Liu Fang (Aquaculture International, 2024)

A high-efficiency solar desalination biomass material prepared by DBD plasma - Jiabao Sun; Yanbin Xin; Tianyu Sun; Bing Sun; Xinfei Fan (Journal of Environmental Chemical Engineering, 2023)

Lab-on-chip separation and biosensing of pathogens in agri-food - Li Xue; Fan Jiang; Xinge Xi; Yanbin Li; Jianhan Lin (Trends in Food Science & Technology, 2023)

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Identification, classification, and evolution of putative xylosyltransferases from algae - Wentao Han; Xiao Fan; Linhong Teng; Michelle Joyce Slade Kaczurowski; Xiaowen Zhang; Dong Xu; Yanbin Yin; Naihao Ye (Protoplasma, 2019)

Inhibition of the adenosinergic pathway: the indispensable part of oncological therapy in the future - Yi Huang; Zili Gu; Yang Fan; Guangxi Zhai; Xiaogang Zhao; Qifeng Sun; Yanbin Shi; Guimei Lin (Purinergic Signalling, 2019)

The hazard risk assessment of regional heavy rainfall over Sichuan Basin of China - Tiangui Xiao; Yongqing Wang; Yanbin Zhao; Fengrong Jing; Zhaoyu Zhan; Li Wang; Jianglin Fan; Weiwei Gan; Xue Yang; Yujie Fang (Natural Hazards, 2017)

Laboratory Investigation of Coal Deformation Behavior and Its Influence on Permeability Evolution During Methane Displacement by CO2 - Jingjing Fan; Ruimin Feng; Jin Wang; Yanbin Wang (Rock Mechanics and Rock Engineering, 2017)

Evaporative enrichment of oxygen-18 and deuterium in lake waters on the Tibetan Plateau - Fasong Yuan; Yongwei Sheng; Tandong Yao; Chaojun Fan; Junli Li; Hui Zhao; Yanbin Lei (Journal of Paleolimnology, 2011)